Perancangan Sistem Informasi Keselamatan dan Kesehatan Kerja (K3) di PT. Multi Jaya Teknik - Pani Irawan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
Occupational Safety and Health (OHS) is an important aspect to ensure worker safety and smooth company operations. This report discusses the design of an OHS information system at PT. Multi Jaya Teknik, which aims to overcome the weaknesses of the manual system, such as incident recording and inefficient OHS training. The system designed based on digitalization includes accident reporting features, training schedule management, and risk evaluation, with design support using UML. As a result, this OHS information system is able to improve data management efficiency, accelerate incident response, and support data-based decision making. The system also helps employees understand occupational safety procedures through structured training, thus creating a safer and more productive work environment. The reporting and risk analysis features support the company in complying with applicable OHS regulations.